Association between paraoxonase 1 -108C/T polymorphism and coronary heart disease: an updated meta-analysis - Liao, Jiadan; Wang, Pengcheng (Frontiers in Cardiovascular Medicine, 2024)
Background:At present, no consensus is reached among articles that investigate the relationship of paraoxonase 1(PON1) -108C/T polymorphism with susceptibility of coronary heart disease(CHD) so far. In this regard, the present meta-analysis was conducted to comprehensively review existing articles related to the relationship of PON1 -108C/T polymorphism with CHD susceptibility.It was preregistered in the International Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY)-INPLASY202430117. Methods:Articles that explored the relationship between PON1 -108C/T polymorphism and CHD incidence were searched from electronic databases according to our preset study selection criteria. Thereafter, we adopted stata 12.0 software to analyze our screened studies. At the same time, odds ratios (ORs) and related 95% confidence intervals (95% CIs) were determined for evaluating association strength. Results:At last, this meta-analysis selected altogether 13 case-control studies that involved 2979 cases and 2887 control subjects. We found that the PON1 -108C/T polymorphism displayed marked relationship with CHD susceptibility (T vs C:OR=1.24,95%CI 1.07-1.45;CT vs CC:OR=1.33,95%CI 1.17-1.52;TT vs CC:OR=1.51,95%CI 1.09-2.09;Recessive model:OR=1.16,95%CI 0.93-1.45; Dominant model:OR=1.45,95%CI 1.16-1.81). Moreover, subgroup analysis showed that race and sample size had no impact on the results. Bioinformatics analysis showed that -108C>T polymorphism was relation to PON1 gene expression(https://gtexportal.org/home/). Conclusions:The PON1 -108T allele is identified as the possible low-penetrant risk factor of CHD, as suggested by our present meta-analysis.